Catalytic hydrogenation products of aromatic and aliphatic dicarboxylic acids - Shinde, Sunil; Deshpande, Raj M. (Asian Journal of Chemistry, 2019)
Hydrogenation of aromatic dicarboxylic acids gave 100 % selectivity to respective cyclohexane dicarboxylic acid with 5 % Pd/C catalyst. 5 % Ru/C catalyst was observed to give over hydrogenation products at 493 K and at lower temperature (453 K) the selectivity for cyclohexane dicarboxylic acids was increased. Hydrogenation of phthalic acid with Ru-Sn/Al2O3 catalyst was observed to give phthalide instead of 1,2-benzene dimethanol or 2-hydroxy methyl benzoic acid. Ru-Sn/Al2O3 catalyst selectively hydrogenated the carboxylic group of cyclohexane dicarboxylic acids to give cyclohexane dimethanol. Use of proper catalysts and reaction conditions resulted in desired products.

Kinetics of hydroformylation of 1-decene using carbon-supported ossified HRh(CO)(TPPTS)(3) catalyst - Pagar, Nitin S.; Deshpande, Raj M. (International Journal of Chemical Kinetics, 2019)
The kinetics of hydroformylation of 1-decene has been investigated using a carbon-supported ossified HRh(CO)(TPPTS)(3)/Ba catalyst in a temperature range of 343-363 K. The effect of concentration of 1-decene, catalyst loading, partial pressure of H-2 and CO, and stirring speed on the reaction rate has been investigated. A first-order dependence was observed for catalyst concentration and hydrogen partial pressure. The rate showed a typical case of substrate inhibition for high 1-decene concentration. The rate varied with a linear dependence on P-CO up to a CO partial pressure of 5-6 MPa in contrast to the general trends; for most of the rhodium-phosphine catalyzed hydroformylation reactions, severe inhibition of rate is observed with an increase in CO pressure. A rate equation has been proposed, which was found to be in good agreement with the observed rate data within the limit of experimental errors. The kinetic parameters and activation energy values have been reported.
Keywords: 1-decene; Hydroformylation; kinetics; ossification; supported ossified

Catalytic hydrogenation of cinnamic acid and salicylic acid - Shinde, Sunil; Deshpande, Raj M. (Asian Journal of Chemistry, 2020)
Hydrogenation of cinnamic acid and salicylic acid was carried out using 5 %Ru/C, 5 % Pd/C and Ru-Sn/Al2O3 catalyst at 493 K and 6.89 MPa of hydrogen partial pressure. Ru-Sn/Al2O3 catalyst was found to be active for hydrogenation -COOH group to give cinnamyl alcohol. The selectivity to cinnamyl alcohol was low (15 %) as absolute inhibition of C=C bond hydrogenation in cinnamic acid is challenging. 5 %Pd/C catalyst was found to hydrogenate C=C bond and aromatic ring in cinnamic acid. 5 %Ru/C catalyst was found to be least selective catalyst as it hydrogenated C=C bond, aromatic ring and -COOH group in cinnamic acid. Hydrogenation of salicylic acid is not possible at 493 K as decarboxylation of salicylic acid occurs.

Kinetics of hydroformylation of camphene using rhodium-phosphite catalyst - Pagar, Nitin S.; Rajurkar, Kalpendra B.; Deshpande, Raj M. (International Journal of Chemical Kinetics, 2020)
Kinetics of hydroformylation of camphene was investigated in the presence of [Rh(CO)(2)(acac)]/P(OPh)(3) catalyst in a temperature range of 363-383 K. The influence of parameters such as stirring speed, camphene, catalyst, ligand concentrations, and partial pressures of H-2 and CO on the activity and selectivity of the catalyst has been studied. The rate showed a first-order dependence with respect to catalyst and camphene concentrations. The effect of partial pressure of hydrogen showed fractional order dependence. The plots of rate versus excess ligand, that is, (P(OPh)(3)) concentration and rate versus CO partial pressure passed through maxima and showed typical substrate/ligand inhibited kinetics. An empirical rate equation has been proposed and found to be in good agreement with the observed rate data. The kinetic parameters and activation energy were also evaluated.
Keywords: camphene; homogeneous; Hydroformylation; kinetics; rhodium-phosphite

Synthesis, characterization and catalytic study of mesoporous carbon materials prepared via mesoporous silica using non-surfactant templating agents - Pagar, Nitin S.; Karandikar, Prashant R.; Chandwadkar, Asha J.; Deshpande, Raj M. (Journal of Porous Materials, 2020)
Mesostructured silica materials with surface area in the range of similar to 700-900 m(2)/g have been prepared using hydroxy-carboxylic acid compounds such as tartaric acid, malic acid and citric acid (low cost non-surfactant template/pore forming agents) and tetraethylorthosilicate (TEOS) as silica source by sol-gel reaction. The templates were removed by either soxhlet extraction or calcination method. Mesoporous carbon molecular sieves were then prepared by carbonizing sucrose inside the pores of the above prepared mesoporous silica using sulfuric acid as a catalyst. The materials were characterized by FTIR spectroscopy, powder X-ray diffraction (XRD), N-2-sorption studies, microanalysis, thermal analysis and transmission electron microscopy (TEM). The resulting carbon material shows relatively higher surface area (similar to 1100 m(2)/g), narrow pore size distribution and pore diameter of 4-5 nm. The mesoporosity of carbon material arises from interconnecting channels arrangements of mesoporous silica template. The mesoporous carbon material was used as a support for the immobilization of rhodium complex [HRhCO(TPPTS)(3)] by ossification method. The prepared catalyst has been tested for the hydroformylation of higher olefins. The activity of the catalyst was improved by 20-30% as compared to the catalyst prepared from a conventional activated carbon support.
Keywords: Carbonization; Hydroformylation; Immobilization; Low cost templates; mesoporous carbon; Mesoporous silica

Kinetics of 1-decene hydroformylation in an aqueous biphasic medium using a water-soluble Rh-sulfoxantphos catalyst in the presence of a cosolvent - Pagar, Nitin S.; Deshpande, Raj M. (International Journal of Chemical Kinetics, 2021)
The kinetics of hydroformylation of 1-decene has been studied in an aqueous biphasic medium using a water-soluble Rh-sulfoxantphos catalyst in the presence of N-methyl pyrrolidone as a cosolvent at 383-403 K. The rate was found to be first order, with concentrations of catalyst and olefin and partial order, with concentrations of hydrogen in the liquid phase. The plot of rate versus excess ligand and CO concentrations passed through maxima, indicating negative order dependence at higher concentrations. These trends have been interpreted based on the established hydroformylation mechanism. High selectivity towards the linear aldehyde was maintained (n: iso ratio > 30). An empirical rate equation has been proposed which was found to be in good agreement with the observed rate data within the experimental error. The activation energy was evaluated to be 74.76 kJ/mol.
Keywords: 1‐ aqueous‐ biphasic; cosolvent; decene; Hydroformylation; kinetics; rh‐ sulfoxantphos